2010
DOI: 10.3109/02656730903341340
|View full text |Cite
|
Sign up to set email alerts
|

Elective re-irradiation and hyperthermia following resection of persistent locoregional recurrent breast cancer: A retrospective study

Abstract: For patients experiencing local recurrence in a previously radiated area, re-irradiation plus hyperthermia following minimisation of tumour burden leads to a high rate of local control, albeit with significant toxicity. The latter might be reduced by a more fractionated re-RT schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 35 publications
2
51
2
Order By: Relevance
“…The effectiveness of re-irradiation plus hyperthermia was reported by Oldenborg et al [36 ]in 2010. 78 patients with breast recurrences were treated with the combined treatment and responded to the therapy.…”
Section: Resultsmentioning
confidence: 98%
“…The effectiveness of re-irradiation plus hyperthermia was reported by Oldenborg et al [36 ]in 2010. 78 patients with breast recurrences were treated with the combined treatment and responded to the therapy.…”
Section: Resultsmentioning
confidence: 98%
“…Radiotherapy at the AMC typically consisted of 32 Gy in 8 fractions given twice per week over a period of 4 weeks; at the BVI, patients received 36 Gy in 12 fractions given 4 times per week. The radiation techniques applied were similar to the standard techniques used for the treatment of recurrent breast cancer, usually photons (6 MV or 10 MV) for the lateral chest wall, axillary, and periclavicular area and electrons (8)(9)(10)(11)(12)(13)(14)(15) MeV) for the anterior chest wall. Hyperthermia was given once per week within 1 hour of radiotherapy at AMC or twice weekly at BVI (Tables 3 and 4).…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Hyperthermia is used frequently to boost the relatively low maximally permitted radiotherapy dose in the treatment of recurrences of breast cancer in previously irradiated areas. [12][13][14] In total, 16 patients with RAS received RT-HT at our institutes. Two of these 16 patients were reported previously in a case report and a letter.…”
mentioning
confidence: 99%
“…Several publications have suggested that hyperthermia with low-dose re-irradiation can achieve good local control for patients who have had all macroscopic disease eradicated prior to radiotherapy. [35]. In the present study we evaluate elective thermoradiotherapy for patients who have had no prior radiotherapy.…”
Section: Introductionmentioning
confidence: 99%